Successful Endoscopic Ultrasound-Guided Alcohol Ablation of Sporadic Insulinoma Using Three-Dimensional Targeting (with Video) - Guru Trikudanathan; Shawn J. Mallery; Stuart K. Amateau (Korean Society of Gastrointestinal Endoscopy, 2016)
Surgical resection is considered the standard of care in the management of symptomatic insulinoma. In this video, we describe the successful management of a symptomatic insulinoma by using linear array endoscopic ultrasound (EUS)-guided ethanol ablation in a poor surgical candidate. EUS-guided ethanol ablation of insulinoma offers a safer, effective, and less invasive alternative to surgery.